Psychiatric care following deliberate self-harm and prospective mortality: evidence from a national cohort of patients in routine care - P. Qin (European Psychiatry, 2022)
Introduction Psychiatric care following self-harm treatment is pivotal in patients´ life both in short- and long-terms.